Analisis Pengaruh Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Sektor Healthcare yang Terdaftar di Indeks Saham Syariah Indonesia - Lathifa Husna; Ruhadi Ruhadi; Hasbi Assidiki Mauluddi; Kristianingsih Kristianingsih (Journal of Applied Islamic Economics and Finance, 2023)
This study was conducted to determine the effect of profitability on firm value in healthcare sector companies listed on the Indonesia Sharia Stock Index (ISSI) 2017-2020. This study is a quantitative study with a causal associative approach using secondary data, the data sample was determined by the purposive sampling method and resulted in a sample of 11 companies with annual financial statements during the 2017-2020 period to obtain 44 observational data. Profitability is proxied by Return on Equity (ROE) and the firm value indicated by Tobin’s Q. This research uses the path analysis method with WarpPLS. The results of the study state that profitability has a significant effect of firm value.